A brief overview of quantitative criminology in Australasia: 1981–1995 - Homel, Ross (Journal of quantitative criminology, 1996)
This paper reviews quantitative criminological research, especially of a sophisticated mathematical nature, published by researchers in Australia and New Zealand since 1981. A statistical analysis of quantitative articles published between 1981 and 1995 in the leading academic journal. The Australian and New Zealand Journal of Criminology , showed that using the five topical categories developed by Farrington (this issue), there has been little change in the types of research carried out, with studies of court processes and correctional issues accounting for two-thirds of papers. The numbers of “simple” and ”sophisticated” quantitative articles as proportions of the total published also did not vary over the 15 years. Areas of strength in quantitative research include drugs, alcohol, and crime; indigenous peoples and the criminal justice system; regulatory law enforcement; the modeling of recidivism; and sentencing. Most sophisticated quantitative research is carried out by noncriminologists, and it appears unlikely that the amount of mathematically sophisticated research will increase significantly in the next few years. Experimental studies and longitudinal designs will probably slowly grow in popularity, and crime prevention will emerge as an area of quantitative strength.